Vowel Harmony, Natural Phonology And The Problems Of Borrowing - Yavas, Mehmet (Kansas Working Papers in Linguistics, 1979)
The analysis of borrowing has created problems for any phonological theory proposed so far. In recent years a new phonological school, Natural Phonology, has claimed to offer a solution to these problems.